Floating Away: The Impact of Hydroelectric Power Stations on Tourists’ Experience in Iceland - Anna Dóra Sæþórsdóttir; C. Michael Hall (Sustainability, 2018)
It is of vital importance that nature-based tourist destinations maintain their natural resources in a sustainable way. Nature and wilderness are the main attractions for tourism in Iceland. The Central Highlands are uninhabited with little visible evidence of human influence except for some huts, gravel roads, and a small number of hydroelectric power plants. However, there are plans for further hydroelectric power development in the area. The Blanda Power Station was constructed in 1991 at the edge of the North Central Highlands. This paper presents the results of a questionnaire survey conducted among tourists in the area in the summer of 2016 with a total of 1078 answered questionnaires. The objective was to estimate the impact of the power station on the experience of tourists and to assess whether their attitude differs from that of tourists in locations where power plant construction has been proposed. The results show that the power plant infrastructure at Blanda, with the exception of transmission lines, does not seem to disturb the experience of the majority of tourists. Tourists at Blanda are also more positive towards power plants than at locations where there are no power plants but where they have been proposed.